Current Progresses in Study of Impacts of the Tibetan Plateau on Asian Summer Climate - 吴国雄 毛江玉 段安民 张琼 (Acta meteorologica Sinica, 2006)
The current progresses in the study of impacts of the Tibetan Plateau on Asian summer climate in the last decade are reviewed. By analyzing evolution of the transitional zone between westerly to the north and easterly to the south （WEB）, it is shown that due to the strong heating over the Tibetan Plateau in spring, the overturning in the prevailing wind direction from easterly in winter to westerly in summer occurs firstly over the eastern Bay of Bengal （BOB）, accompanied with vigorous convective precipitation to its east. The area between eastern BOB and western Indo-China Peninsula thus becomes the area with the earliest onset of Asian monsoon, which may be referred as BOB monsoon in short. It is shown that the summertime circulations triggered by the thermal forcing of the Iranian Plateau and the Tibetan Plateau are embedded in phase with the continental-scale circulation forced by the diabatic heating over the Eurasian Continent. As a result, the East Asian summer monsoon is intensified and the drought climate over the western and central Asian areas is enhanced. Together with perturbations triggered by the Tibetan Plateau, the above scenarios and the associated heating have important influences on the climate patterns over Asia. Furthermore, the characteristics of the Tibetan mode of the summertime South Asian high are compared with those of Iranian mode. Results demonstrate that corresponding to each of the bimodality of the South Asian high, the rainfall anomaly distributions over Asia exhibit different patterns.